2018
DOI: 10.1002/icd.2092
|View full text |Cite
|
Sign up to set email alerts
|

The Grasping Task: A 12‐month predictor of 24‐month delay task performance and BRIEF‐P inhibition scores

Abstract: Important developments in executive function are thought to occur during the second year of life, but few tools exist to assess executive function in this period. We argue that, to be effective, tasks for this age range need to reduce the abstract nature of the task rules and reduce reliance on verbal instruction. We present the Highlights • We assessed the predictive validity of the grasping task, a new measure of emerging inhibitory skills in infancy.• Grasping task scores at 12 months predicted children's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Despite significant research on ATDG during early childhood, little work has examined responses to food delay tasks during infancy ( 48 ). Prior research has used familiar and motivating objects to test infant delay capacity ( 13 ), but researchers interested in the development of eating behavior regulation have emphasized the importance of using food-specific tasks ( 2 , 10 ). The ATDG-FIT was therefore designed to mirror ATDG-for-food tasks in older children by using milk and a familiar object (bottle or breast) to elicit infant responses while waiting to be fed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant research on ATDG during early childhood, little work has examined responses to food delay tasks during infancy ( 48 ). Prior research has used familiar and motivating objects to test infant delay capacity ( 13 ), but researchers interested in the development of eating behavior regulation have emphasized the importance of using food-specific tasks ( 2 , 10 ). The ATDG-FIT was therefore designed to mirror ATDG-for-food tasks in older children by using milk and a familiar object (bottle or breast) to elicit infant responses while waiting to be fed.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviors that can be measured during infancy may be relevant for understanding, predicting, and ultimately shaping later eating behavior regulation. For example, Neale et al ( 13 ) used a spoon grasping task with 12-month-olds which required inhibiting their response to grasp a spoon facing the wrong direction, and instead grasp the spoon handle in order to obtain food. Responses on this task at 12 months predicted ATDG for food at 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…A new task to assess children's inhibitory/effortful control was developed during an earlier phase of this study, as reported in Neale et al (2018). The child was seated in a high chair.…”
Section: The Grasping Task (12-months)mentioning
confidence: 99%
“…the inhibitory control applied is (at least in some cases) volitional rather than automatic. For full details on development, administration and coding of this task see Neale et al (2018).…”
Section: The Grasping Task (12-months)mentioning
confidence: 99%
See 1 more Smart Citation